2012
DOI: 10.1111/j.1468-3083.2012.04636.x
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for treatment of atopic eczema (atopic dermatitis) Part II

Abstract: The existing evidence for treatment of atopic eczema (atopic dermatitis, AE) is evaluated using the national standard Appraisal of Guidelines Research and Evaluation. The consensus process consisted of a nominal group process and a DELPHI procedure. Management of AE must consider the individual symptomatic variability of the disease. Basic therapy is focused on hydrating topical treatment, and avoidance of specific and unspecific provocation factors. Anti-inflammatory treatment based on topical glucocorticoste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
343
0
36

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 348 publications
(385 citation statements)
references
References 176 publications
(289 reference statements)
3
343
0
36
Order By: Relevance
“…Глюкокортикостероиды имеют многочисленные эф -фекты при воздействии на кожу [32][33][34]. Молекула сте-роида после поглощения связывается с цитоплазмати-ческим рецептором в кератиноцитах, который затем проникает в ядро, воздействуя на транскрипцию рибо-нуклеиновой кислоты.…”
Section: топические глюкокортикостероидыunclassified
“…Глюкокортикостероиды имеют многочисленные эф -фекты при воздействии на кожу [32][33][34]. Молекула сте-роида после поглощения связывается с цитоплазмати-ческим рецептором в кератиноцитах, который затем проникает в ядро, воздействуя на транскрипцию рибо-нуклеиновой кислоты.…”
Section: топические глюкокортикостероидыunclassified
“…The atopic diseases are chronic inflammatory disorders caused by aberrant T helper 2 (Th2) immune responses against common innocuous environmental antigens in susceptible individuals. The importance of a delicate balance between allergen -specific T-reg cells and allergen-specific Th2 cells in healthy and allergic immune responses to common environmental allergen was demonstrated in study of Atkis et al [8,9].…”
Section: Role Of Probiotics In Atopic Dermatitismentioning
confidence: 99%
“…Recent studies showed that probiotics can also exert beneficial effects by directly modulating immune system. The treatment with certain probiotics may prevent and improve symptoms of experimental atopic dermatitis, inflammatory bowel disease and asthma by down regulating inflammatory cytokines inducing immune regulatory mechanism [9,11].…”
Section: Role Of Probiotics In Atopic Dermatitismentioning
confidence: 99%
“…As a treating physician, often the major obstacle is not finding a suitable treatment but finding a way to reach the patient and parent in order to have a good understanding of the disease and its treatment and good adherence [6][7][8]. It is well known that education [9][10][11][12][13][14][15] as seen in eczema schools and not only for diseases such as eczema [16] but also other educational measures [15,17,18] at least temporarily enhances compliance. How the eczema school works in different countries and cities depend often on the local clinicians, the facilities found and cultural differences [13,[19][20][21].…”
Section: Introductionmentioning
confidence: 99%